Approximation of ( ψ, β )-differentiable functions defined on the real axis by Weierstrass operators - Kalchuk, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Asymptotic equalities are obtained for upper bounds of approximations by the Weierstrass operators on the functional classes $\widehat{C}^{ψ}_{β, ∞}$ and $\widehat{L}^{ψ}_{β, 1}$ in metrics of the spaces $\widehat{C}$ and $\widehat{L}_1$, respectively.